Limit load solutions for sen(t) specimens - 2d and 3d problems - Graba, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the limit load solutions for SEN(T) specimens under plane stress and plane strain conditions. The existing solutions are verified using the Finite Element Method and extended to 3D cases. The numerical results can be used to assess the strength of a structural element with a defect. This paper is a verification and extension of the author`s previous paper.
Keywords: SEN(T); limit loads; FEM; fracture